Analysis of Desires of the Main Character in the Short Story “Ein Tisch ist ein Tisch” by Peter Bichsel: A Study of Deleuze and Guattari’s Schizoanalysis - M. Kharis; Rosyidah Rosyidah; Sawitri Retnantiti (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
This study aims to describe the desires of the main character ‘der Mann’ in the short story by Peter Bichsel using Deleuze and Guattari’s Schizoanalysis theory. This was a qualitative study with a descriptive approach. The research data were comprised of words, phrases, and sentences. The collected data were subsequently categorized into types of desires. Data were analyzed using reading and recording techniques and described based on the proportion of desires. The results of the analysis showed that the main character receives constant pressures from society, leading to the emergence of paranoid desire, a desire that is formed due to the pressure of particular systems or social codes outside of the main character. This desire is schizophrenic at the individual level. In the short story, this desire is manifested through the creation of a new language by ‘der Mann’. In the end, the main character ‘der Mann’ can use new vocabulary at the levels of phrases and sentences, but unable to influence other language users. As a result, his newly self-created language is unacceptable in society. However, the schizophrenic desire at the individual level has the potential to destruct social formation